2002
DOI: 10.1530/rep.0.1230067
|View full text |Cite
|
Sign up to set email alerts
|

Cell death during natural and induced luteal regression in mares

Abstract: In mares, little information is available on the type of cell death that occurs during natural and induced luteal regression. Corpora lutea were collected from mares in the early luteal phase, days 3-4 (n = 4); mid-luteal phase, day 10 (n = 5); early regression, day 14 (n = 4); late regression, day 17 (n = 4); and 12 and 36 h (n = 3 per group) after PGF2alpha administration on day 10. Histological and ultrastructural sections were examined and TUNEL was used to detect DNA fragmentation. In early luteal regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Morphological alterations of both steroidogenic cells and blood vessels are essential for regression of cyclic CL [8], with microvascular endothelial cells being the first ones to undergo apoptosis [58]. Since in the mare, overall apoptosis also increases in the late luteal phase CL [59,60], it makes sense that in this study vascular regression was also increased in this stage of the luteal phase, as shown by a decrease in both microvascular areas and endothelial cell mitogenesis under the influence of PGF 2␣ . In conclusion, vascular growth and regression appear to be coordinated with development of non vascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological alterations of both steroidogenic cells and blood vessels are essential for regression of cyclic CL [8], with microvascular endothelial cells being the first ones to undergo apoptosis [58]. Since in the mare, overall apoptosis also increases in the late luteal phase CL [59,60], it makes sense that in this study vascular regression was also increased in this stage of the luteal phase, as shown by a decrease in both microvascular areas and endothelial cell mitogenesis under the influence of PGF 2␣ . In conclusion, vascular growth and regression appear to be coordinated with development of non vascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of neutrophils and macrophages in the CL using the periodic acid-Schiff reaction Formalin-fixed sections (5 mm) of the luteal tissue samples were stained with periodic acid-Schiff (PAS) reagent (Sigma) for 10 min and then counterstained with haematoxylin as previously described (Al-Zi'abi et al 2002, Jiemtaweeboon et al 2011. In general, it is recognised that PAS staining is a useful method to detect granulophilic leukocytes.…”
Section: Western Blottingmentioning
confidence: 99%
“…It is determinant for normal reproductive function and development in the ovary [11]. This process has been reported in CL involution in several species, such as mouse [12,13], rat [14,15], rabbit [16,17], sheep [18,19], cow [20,21], pig [22], human [23], and mare [24,25].…”
Section: Introductionmentioning
confidence: 96%